2009
DOI: 10.1136/bmj.b2538
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of COX 2 selective inhibitors and traditional NSAIDs alone or in combination with a proton pump inhibitor for people with osteoarthritis

Abstract: Objectives To investigate the cost effectiveness of cyclooxygenase-2 (COX 2) selective inhibitors and traditional non-steroidal anti-inflammatory drugs (NSAIDs), and the addition of proton pump inhibitors to these treatments, for people with osteoarthritis. Design An economic evaluation using a Markov model and data from a systematic review was conducted. Estimates of cardiovascular and gastrointestinal adverse events were based on data from three large randomised controlled trials, and observational data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 37 publications
2
90
0
7
Order By: Relevance
“…In the clinical scenario where the above patient has had an upper GI bleed within the past year and the practitioner still chooses to use an oral NSAID, the TEP strongly recommends using a COX-2 selective inhibitor in combination with a proton-pump inhibitor. Subsequent to the initial meeting of the TEP, Latimer and colleagues reported that the addition of a proton-pump inhibitor to either a nonselective or COX-2 selective NSAID is cost effective given the evolving evidence base for efficacy and reductions in price (30). Therefore, whenever an NSAID is used for the chronic management of patients with knee or hip OA, the practitioner should consider adding a proton-pump inhibitor to reduce the risk of development of symptomatic or complicated upper GI events.…”
Section: Resultsmentioning
confidence: 99%
“…In the clinical scenario where the above patient has had an upper GI bleed within the past year and the practitioner still chooses to use an oral NSAID, the TEP strongly recommends using a COX-2 selective inhibitor in combination with a proton-pump inhibitor. Subsequent to the initial meeting of the TEP, Latimer and colleagues reported that the addition of a proton-pump inhibitor to either a nonselective or COX-2 selective NSAID is cost effective given the evolving evidence base for efficacy and reductions in price (30). Therefore, whenever an NSAID is used for the chronic management of patients with knee or hip OA, the practitioner should consider adding a proton-pump inhibitor to reduce the risk of development of symptomatic or complicated upper GI events.…”
Section: Resultsmentioning
confidence: 99%
“…126 Despite the availability of inexpensive NSAID treatment options, this potential financial benefit may be offset by the cost associated with preventing or treating NSAID-related complications. 128,129 Numerous studies have compared the safety, effectiveness, and cost of competing strategies regarding celecoxib versus traditional NSAIDs alone or in combination with gastroprotective agents. Studies confirm the efficacy of gastroprotective agents such as PPIs in preventing NSAID-induced gastrointestinal complications.…”
Section: Balancing the Risks: Use Of Nsaids In Patients With Gastroinmentioning
confidence: 99%
“…128,133 Economic models indicate a gastroprotective agent should be given with traditional NSAIDs and coxibs. 129,141 In efforts to control costs, managed care organizations and Medicaid programs have implemented utilization management strategies, such as tier placement, prior authorization, and step therapy to restrict the use of celecoxib. Studies have shown that these tools effectively reduce utilization and expenditures for the drug, but whether these restrictions confer positive health outcomes and lower costs is not clear.…”
Section: Balancing the Risks: Use Of Nsaids In Patients With Gastroinmentioning
confidence: 99%
“…Proton-pump inhibitors should be prescribed for their gastroprotective effects when NSAIDs are used for chronic pain management for knee OA. (13,14) If pain control is still not achieved, tramadol is added.…”
Section: Analgesiamentioning
confidence: 99%